Management of Indigenous Toys, Modern Toys and Animation For Early Childhood Education In Rivers State, Nigeria. - Ukala, Chinyere Catherine (Advances in Social Sciences Research Journal, 2020)
This study examined the management of indigenous toys, modern toys and animation for early childhood education. Three research questions and three hypotheses guided the study. The study adopted a description survey design with a population of 655 primary schools that house early childhood centres spread across the 23 Local Government Areas of Rivers State. A sample size of 164 head teachers in early childhood education centres was drawn using stratified random sampling technique representing 25% of the population. A self-designed instrument titled Management of Indigenous Toys, Modern Toys and Animation for Early Childhood Education Questionnaire (MITMAFECEQ) was used for data collection. Face and content validities of the instrument were done by experts in the related areas while reliability coefficient of 0.88 was computed through Cronbach internal consistency reliability technique. Mean and standard deviation were used to answer the research questions while z-test was used to test the null hypotheses at 0.05 alpha level of significance. It was found among others that the management of indigenous toys enhances spatial, numeric and logical development and reasoning while management of modern toys increase the development of electronic skills among pupils. It was recommended among others that early childhood education can be achieved through proper use of indigenous toys in order to instil manual calculation ability in children. The children should be allowed access to modern toys and animation in order to enhance their prowess and dexterity in handling life events and facing future life's challenges in this digital world of 21st century.